The revision of Brussels I Regulation and the abolition of exequatur - Miha Žebre (LeXonomica, 2021)
Council Regulation (EC) No 44/2001 of 22 December 2000 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters1 (hereinafter referred to as »Brussels I Regulation« or »Regulation«) is, according to Professor Dr. Hess,2 one of the most successful pieces of Union legislation. Indeed, the fact that the rules contained in Regulation have, in one act3 or another, survived almost 42 years without major conceptual revision, is impressive. However, it is interesting to note that at each stage of the Regulation’s evolution, the underlying rationale for the Regulation itself has varied. Initially, the impetus of the Brussels Convention, namely the stimulation of cross-border trading within the EEC, served as a platform for the Regulation ...